Complete Sonatas for Pianoforte Solo - Schubert, Franz (Dover Publicatons, Inc., 1970)
Di dalam buku ini terdapat lagu: Sonata in E Major; Sonata in C Major; Sonata in A-flat Major; Sonata in E Minor; Sonata in B Major, Op. 147; Sonatain A Minor, Op. 164; Sonata in E-flat Major, Op.122; Sonata in A Minor, Op.143; Sonata in A Minor, Op.42; Sonata in A Major, Op.120; Sonata in D Major, Op.53; Sonata in G Major, Op. 78; Sonata in C Minor; Sonata in A Major; Sonata in B-flat Major.